2020
DOI: 10.1002/adfm.202009136
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Transparent Supercapacitors: Materials and Devices

Abstract: The progressive development of flexible transparent portable electronic devices is in urgent need of matching power sources. Flexible transparent supercapacitors (FTSCs) are the core resources due to their high optical transmittance, endurable mechanical flexibility, excellent electrochemical performance, and facilely accessible device configuration. This review organizes the rational design of nanostructured electrode materials toward FTSCs. First, the structure, mechanism, and property of FTSCs are introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 304 publications
(293 reference statements)
0
134
0
Order By: Relevance
“…The areal capacitances calculated from the CV curves were 0.09 mF/cm 2 for the AACS NW electrode and 4.3, 8.7, and 12.2 mF/cm 2 for Ag/Au/MnO 2 core–shell NW electrodes. The areal capacitances were calculated according to , where is the current, and are the initial and final voltage of the CV curve, ν is the scan rate, and is the geometric area of the electrode [ 26 ]. To identify the charge-storage mechanism of the suggested Ag/Au/MnO 2 core–shell NW electrode, we conducted additional CV tests in various voltage scan rates, as shown in Figure S9a .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The areal capacitances calculated from the CV curves were 0.09 mF/cm 2 for the AACS NW electrode and 4.3, 8.7, and 12.2 mF/cm 2 for Ag/Au/MnO 2 core–shell NW electrodes. The areal capacitances were calculated according to , where is the current, and are the initial and final voltage of the CV curve, ν is the scan rate, and is the geometric area of the electrode [ 26 ]. To identify the charge-storage mechanism of the suggested Ag/Au/MnO 2 core–shell NW electrode, we conducted additional CV tests in various voltage scan rates, as shown in Figure S9a .…”
Section: Resultsmentioning
confidence: 99%
“…After 500 times repeated bending cycles, the capacitance was maintained at 94%, confirming the mechanical stability and flexibility of the suggested Ag/Au/MnO 2 core–shell NW network electrodes. Finally, we evaluated the performance of the fabricated flexible supercapacitor through a Ragone plot, as shown in Figure 6 d. The energy and power density were calculated according to and , respectively [ 26 ]. From the Ragone plot, it was confirmed that the suggested Ag/Au/MnO 2 flexible supercapacitor was able to store 0.41 μWh/cm 2 at 12.9 μW/cm 2 , which is comparable (or even better) to some of the previously reported flexible supercapacitors using various materials such as the MnO 2 /Au (4.2 μWh/cm 2 at 0.51 μW/cm 2 ), the GO/CNT (25.5 nWh/cm 2 at 1.25 μW/cm 2 ), the rGO/Cu-MOF (0.51 μWh/cm 2 at 2.54 μW/cm 2 ), the ZnO NW (0.03 μWh/cm 2 at 14 μW/cm 2 ), and the MnO 2 /Ti3C2Tx MXene (0.7 μWh/cm 2 at 80.0 μW/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible electronic devices with prominent scalability and portability have been proposed for use in a wide array of wearable devices, electronic skins, smart textiles, and others [1,2]. The development of flexible electronic devices strictly relies on stretchable functional components and energy storage modules.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, flexible, lightweight, and environmentally friendly electrodes for SCs have attracted increasing attention since they meet the needs for portable (e.g., foldable phones) and wearable (e.g., smart textiles) electronics [ 24 , 25 , 26 , 27 ]. In these devices, which exhibit high specific energy and power densities and long life cycles, all components, including the electrodes, are flexible.…”
Section: Introductionmentioning
confidence: 99%